Key Issues for Realizing Open Ecoacoustic Monitoring in Australia - Vella, Kellie; Capel, Tara; Gonzalez, Ashleigh; Truskinger, Anthony; Fuller, Susan; Roe, Paul (Frontiers in Ecology and Evolution, 2022)
Many organisations are attempting to scale ecoacoustic monitoring for conservation but are hampered at the stages of data management and analysis. We reviewed current ecoacoustic hardware, software, and standards, and conducted workshops with 23 participants across 10 organisations in Australia to learn about their current practices, and to identify key trends and challenges in their use of ecoacoustics data. We found no existing metadata schemas that contain enough ecoacoustics terms for current practice, and no standard approaches to annotation. There was a strong need for free acoustics data storage, discoverable learning resources, and interoperability with other ecological modelling tools. In parallel, there were tensions regarding intellectual property management, and siloed approaches to studying species within organisations across different regions and between organisations doing similar work. This research contributes directly to the development of an open ecoacoustics platform to enable the sharing of data, analyses, and tools for environmental conservation.